Pengaruh Food Vlogger Terhadap Perilaku Konsumsi Mahasiswa - Pathmi Noerhatini (Jurnal Bisnisman : Riset Bisnis dan Manajemen, 2025)
The continuous growth and prevalence of food vlogger content has a notable influence on consumer behaviours within the Food and Beverage (F&B) industry. This influence also extends to students at ITB Ganesha. This study explores the impact of food vloggers on the food and beverage consumption behaviours of ITB Ganesha students. The research was conducted from November 2023 to March 2024. A mixed-method approach was employed, combining qualitative and quantitative analyses. Primary data were collected through questionnaires completed by 100 ITB Ganesha students. Most respondents reported watching food vlogger content on the YouTube platform, with an average viewing time of approximately one hour per day. The processed data revealed a positive correlation between food vlogger content and consumer behaviours. Variables such as physical attractiveness, expertise, and trustworthiness were found to positively influence consumer attitudes toward the product, particularly when vloggers expressed favourable responses or endorsements of the featured food or beverage. The results also indicate that food vloggers assist viewers in making decisions about where to eat and help assess the perceived quality of restaurants. Overall, this study aligns with the United Nations Sustainable Development Goal (SDG) 3: Good Health and Well-Being, by highlighting how digital food content can shape healthier and more informed consumption choices.